Language arts workshop purposeful reading and writing instruction - Frey, Nancy 1959- (Pearson/Merrill/Prentice Hall, 2006)
"Language Arts Workshop: Purposeful Reading and Writing Instruction presents a manageable way of organizing instruction by exploring a gradual release of responsibility from teacher to student. This is accomplished through meaningful experiences in all areas of need for literacy development, including oral language, spelling, vocabulary, word study, fluency, and comprehension. As in an apprenticeship, novice readers and writers learn a craft under the guidance of a skilled and knowledgeable teacher. Through the language arts workshop, students read and write every day, spending time working with their teacher, collaborating with peers, and working independently."--Book jacket.